Border management and organised crime at south Africa’s ports of entry: Challenges and strategies for effective control - Mugambiwa, Shingirai; Rakubu, Kholofelo (Edelweiss Applied Science and Technology, 2025)
Effective border control is crucial in protecting people and providing economic security and sovereignty among nations. Countries face a plethora of threats from organized crime such as human trafficking, terrorism, and smuggling of illicit goods, which are serious challenges to any country’s security and independence, and hence the need to deal with such crimes. This paper seeks to examine border control and patrol in South Africa, focusing largely on the emerging issues of illegal migration and transnational crime. The paper utilized a qualitative desktop method and exploratory design by examining the existing literature on the topic. A comprehensive content analysis of twenty (20) peer-reviewed articles that were deemed pertinent to border security and organized crime within the framework of South African ports of entry was employed. A thematic analysis approach was adopted by categorizing the articles according to shared themes or techniques. The paper emphasized the significance of establishing adaptable border management systems that include high-tech technologies, joint initiatives of various authorities, and participation of surrounding populations to increase security assurances at the ports of entry. The paper outlines the need for policy reforms and measures that should be put in place to fight such issues as globalization presents more challenges that need to be tackled.